ASEAN integration remains an illusion - Desker, Barry (2016)
As ASEAN enters a critical year in which it has to declare itself as a single ASEAN Community, a fundamental question needs to be asked: Is ASEAN integration a growing reality or an aspiration that remains unfulfilled?